Edukasi Program Kampung Iklim Dalam Mewujudkan Desa Tanggap Perubahan Iklim di Negara Bagian Terengganu Darul Iman Malaysia: Edukasi Program Kampung Iklim Dalam Mewujudkan Desa Tanggap Perubahan Iklim di Negara Bagian Terengganu Darul Iman Malaysia (UIR PRESS, 2025)
This community service aims to increase understanding and community involvement in dealing with climate change through the education of the Climate Village Programme (ProKlim) in the State of Terengganu Darul Iman, Malaysia. The program is designed to build community awareness of the impacts of climate change and encourage real action in mitigation and adaptation to sustainable mitigation and adaptation to a sustainable environment. Activities include socialization, training, and mentoring related to natural resource management, energy efficiency, greenhouse gas emission reduction, and environmentally friendly practices. Energy efficiency, greenhouse gas emission reduction, and environmentally friendly practices such as sustainable agriculture and community-based waste management. Such as sustainable agriculture and community-based waste management. Through the education of the climate village program in Terengganu State, Darul Iman Malaysia, it has been shown that increased community understanding and participation in adopting pro-environmental in adopting pro-environmental behaviors. The program's success is key to support from local government, academia, and other stakeholders. The success of this program. With continuous education and active community participation, it is hoped that the villages in Terengganu active participation of the community, it is hoped that the villages in Terengganu can become a model of an empowered and sustainable that are empowered and sustainable Keywords: Education, Climate Village Programme